2016
DOI: 10.1515/jos-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Mixed-Source Statistics as Affected by Classification Errors

Abstract: Publications in official statistics are increasingly based on a combination of sources. Although combining data sources may result in nearly complete coverage of the target population, the outcomes are not error free. Estimating the effect of nonsampling errors on the accuracy of mixed-source statistics is crucial for decision making, but it is not straightforward. Here we simulate the effect of classification errors on the accuracy of turnover-level estimates in cartrade industries. We combine an audit sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…It mostly contains elementary probability manipulations. We make one simplifying assumption compared to [19]: the probabilities p ghi do not depend on i. We write p gh instead and only a single contingency matrix P remains.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It mostly contains elementary probability manipulations. We make one simplifying assumption compared to [19]: the probabilities p ghi do not depend on i. We write p gh instead and only a single contingency matrix P remains.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it can be shown that equation (1.2) holds for a multi-class variable s and any numerical variable y, with P being the K × K contingency matrix [19]. We now make two crucial observations.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Both reasons imply that the probability of a classification error (more specifically, a false negative classification error) increases as turnover decreases. However, we make the assumption because accurately estimating P for different turnover classes, as suggested by Van Delden et al (2016), requires a far larger training data set than the training data set that we have available.…”
Section: Classification Error Modelmentioning
confidence: 99%
“…If we assume the classification error model, it follows that E.â i / = P T a i and therefore To estimate the bias as given in expression (7), we could use the plug-in estimator B 0 = .P T − I 2 /ŷ: . 8/ Following Van Delden et al (2016), we assume that E.P T / = P T and thatP T andŷ are uncorrelated. It follows that E.B 0 / = P T B.ŷ/; hence the plug-in estimator is a biased estimator of the bias.…”
Section: Estimating Bias and Variancementioning
confidence: 99%